Political Marketing Success: An Investigation on 2015 Iranian Parliamentary Elections - Ashtiani, Seyed Mohsen Lotfi; Ashtiani, Seyed Mohammad Hossein Lotfi; Ashtiani, Seyed Ahmad Lotfi (Journal of History Culture and Art Research, 2017)
This study investigates factors affecting the success of political marketing by basing on a fieldwork. To evaluate proposed hypotheses, a questionnaire was used to collect data. This research’s statistical society includes citizens of Arak city by using proportional sampling method and reaches 287 completed questionnaires. According to the data analysis, the results indicate that the market–oriented strategy adoption, doing of effective research about voters, voters division, candidates status and creation and management of mental image have the positive effect on the political marketing. Given the importance of political marketing and proper use of the marketing techniques in the campaigns and realizations of successful political marketing, this study introduces advantages of political marketing and explains how to use it and provides a conceptual model.